THE METHOD OF ESTIMATING THE PROBABILITY CHARACTERISTICS OF QUADRUPOLE RELIABILITY - Е. I. Sukach (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The technique estimates the probability characteristics of the reliability of multicomponent complex systems with two inputs and two outputs, by the probabilistic characteristics of the reliability of their components. The technique is versatile and allows for a transition to the calculation of exact probability characteristics of systems reliability with any number of inputs and outputs.